T is for trespass [compact disc, unabridged] - Grafton, Sue (Grafton, Sue. Kinsey Millhone mysteries., 2007)
Private investigator Kinsey Millhone searches for sociopath Solana Rojas, an identity she stole that gives her access to private caregiving jobs.